FAT1 mutations cause a glomerulotubular nephropathy - Heon Yung Gee (Nature Portfolio, 2016)
Steroid-sensitive nephrotic syndrome (SRNS) can cause CKD and necessitate kidney transplant. Here the authors identify FAT1 mutations by homozygosity mapping and whole-exome sequencing in families with SRNS and provide functional mouse and zebrafish evidence that FAT1 is required for normal glomerular and tubular function and that FAT1 mutations can cause SRNS.